What is the Role of the Geriatrician in Home Health Care?: An_x000D_ Overview Through an International Survey - TUFAN ÇİNÇİN, ASLI (My University, 2020)
Objective: To conduct an international survey among geriatricians on their current home care practice and opinions on the role of geriatricians in_x000D_ home care._x000D_ Materials and Methods: A survey consisting of 11 multiple-choice questions was administered to geriatricians from Turkey, Europe and the United_x000D_ States of America (USA) between January 2016 and March 2016. The survey included questions about the current practice of geriatricians in home_x000D_ care, Geriatric syndromes they observe in home care patients, opinions on whether the general practitioner should report the medical condition of_x000D_ home care patients to the geriatrician, what the geriatrician’s role should be and components of the comprehensive assessment form which should_x000D_ be included in home health care. Answers were collected in a single center._x000D_ Results: Forty-three geriatricians from Turkey and 18 geriatricians from five different European countries and the USA participated in the survey._x000D_ Forty-four percent (n=27) stated that they currently offer visits to home care patients. Eighty-two percent (n=50) of participants thought that_x000D_ geriatricians should provide consultations to home care patients and 44.3% (n=27) thought that geriatricians should visit patients directly._x000D_ Conclusion: Almost 45% of geriatricians visit home care patients in their current practice. Nearly 85% of geriatricians thought that the general_x000D_ practitioner should report the medical condition of home care patients to the geriatrician, along with annual comprehensive geriatric assessment._x000D_ Serving as a “consultant physician” was agreed upon by more than 80% of participants regarding the role of geriatricians in the practice of home_x000D_ care.